1991
DOI: 10.1111/j.1365-2427.1991.tb00512.x
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study of the breakdown of submerged leaves by hyphomycetes and invertebrates in Morocco

Abstract: 1. Mechanisms of the breakdown of submerged leaves under the warm and dry Moroccan climate, including the interaction between hyphomycetes and invertebrates, were investigated.2. Laboratory experiments were performed on dried leaves of Salix sp. and Nerium oleander.3. During the first month under the experimental conditions, Melanopsis praemorsa, Physa acuta (Gastropoda) and Hydropsyche maroccana (Trichoptera), respectively, were responsible for a loss of weight of 38, 21 and 13% in willow leaves, and 40, 15 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 49 publications
1
25
0
Order By: Relevance
“…We believe that Hydropsyche maroccana would be better classified as both a shredder and a filterer. In fact, Chergui & Pattee (1991) reached the same conclusion following an experimental study : they found that the dried leaves of willow and oleander incubated in the presence of Hydropsyche maroccana lost 13 % and 8 % of their initial weight, respectively, in 30 days. In summer, Trichoptera dominated in the absence of any trophic competition.…”
Section: Decomposition Of Willow Leavessupporting
confidence: 54%
See 1 more Smart Citation
“…We believe that Hydropsyche maroccana would be better classified as both a shredder and a filterer. In fact, Chergui & Pattee (1991) reached the same conclusion following an experimental study : they found that the dried leaves of willow and oleander incubated in the presence of Hydropsyche maroccana lost 13 % and 8 % of their initial weight, respectively, in 30 days. In summer, Trichoptera dominated in the absence of any trophic competition.…”
Section: Decomposition Of Willow Leavessupporting
confidence: 54%
“…The dependence of invertebrates activity on that of aquatic hyphomycetes was shown by Chergui & Pattee (1991) who found that the percentage of assimilation by Melanopsis praemorsa was greater when willow leaves were conditioned by Lemonniera aquatica. The percentage of assimilation was very low in the presence of Tetracladium marchalianum.…”
Section: Decomposition Of Willow Leavesmentioning
confidence: 98%
“…The prosobranch gastropod Melanopsis, whose impact has been extensively demonstrated by Chergui & Pattee (1991a, 1991b, 1992, was dominant in the Sebou where it was present even in the deeper sediment strata. Thus faster breakdown in this site may be explained simultaneously by greater current velocity, coarser substratum, and their consequences: interstitial water flow, higher oxygen concentration, and the presence of shredders at all depths.…”
Section: Discussionmentioning
confidence: 97%
“…As the state in which most plant litter reaches the water in the semiarid Northeastern Moroccan climate is still uncertain (Chergui & Pattee 1991b), the leaves were dried to constant weight at 40 °C for 48 h, then weighed to the nearest 0.2 mg by batches of 2 or 3 g and enclosed in plastic bags until they were used.…”
Section: Collection Of Leavesmentioning
confidence: 99%
“…Shredders in these streams may choose their food sources in function of their nutritional needs, and can feed preferentially on the leaves that are richer initially or that are enriched faster in terms of microbial colonization. When given a choice, shredders preferentially feed or colonize certain leaf species such as alder, or leaves there are already conditioned by microorganisms (CHERGUI and PATTEE, 1991;GRAÇA, 1992, 1995;GRAÇA et al, 1993;NOLEN and PEARSON, 1993). By incorporating leaves into secondary production, they accelerate leaf fragmentation and produce abundant fecal pellets, a source of FPOM to downstream invertebrates (GRAÇA, 2001).…”
Section: Introductionmentioning
confidence: 98%